Energy-efficient CO2 hydrogenation with fast response using photoexcitation of CO2 adsorbed on metal catalysts - Chanyeon Kim (Nature Portfolio, 2018)
While many heterogeneous chemical transformations require high temperatures, such conditions are costly and corrosive to the catalysts. Here, authors enhance CO2 hydrogenation over metal nanoparticles by light irradiation via an unusual mechanism and reduce the reaction’s energetic demands.